The Philippine Sustainable Development Network (Philippines) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Philippine Sustainable Development Network (PSDN) holds quarterly, one-day training sessions in email and Internet use, web mastering and content.